2007
DOI: 10.1001/archinte.167.6.606
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Proactive System to Improve Breast Cancer Screening

Abstract: Background: Screening mammography is recommended for early detection of breast cancer but screening rates remain suboptimal.Methods: A primary care portal for a large academic primary practice was developed for all preventive services. Another Web-based system (PRECARES [PREventive CAre REminder System]) was developed for appointment secretaries to manage proactive breast cancer screening. Female patients aged 40 to 75 years were randomly assigned to a control group (usual care) and an intervention group. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 23 publications
(33 reference statements)
0
42
1
2
Order By: Relevance
“…Breast cancer screening rates were significantly better when using an automated clinical prompt. 9 Similar improvement in screening for abdominal aortic aneurysms was noted using programmed reminders. 10 Clinical reminders positively affected osteoporosis screening rates.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Breast cancer screening rates were significantly better when using an automated clinical prompt. 9 Similar improvement in screening for abdominal aortic aneurysms was noted using programmed reminders. 10 Clinical reminders positively affected osteoporosis screening rates.…”
mentioning
confidence: 69%
“…The GDMS extracts information from the electronic medical record to improve patient care with rulesbased reminders for preventative services, diabetes, and coronary artery disease care. 9 The application is frequently revised to include updated recommendations. In the ECH practice, a summary of GDMS recommendations is printed at each patient visit to enable the clinician to discuss recommendations with the patient.…”
Section: Methodsmentioning
confidence: 99%
“…However, similar screening rates were achieved with significantly fewer reminder letters in intervention practices where PCPs reviewed their overdue patients, and intervention PCPs reported spending less time during clinic hours on cancer screening tasks. Studies have shown that involvement of a PCP [23][24][25][26][27][28] and non-visit-based reminder systems 10,[12][13][14][15][16][17]36,37 can increase rates of preventive cancer screening. The current study demonstrates that an automated reminder IT application without physician input led to similar screening rates for patients who seemed to be overdue for up to 3 widely recommended cancers: breast, cervical, and colorectal.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Non-visit-based reminder systems for cancer screening, including those using health information technology (IT), have been shown to increase screening rates but generally focus on only a single condition. [12][13][14][15][16][17] We showed improved screening rates using a population management system in which primary care providers (PCPs) reviewed a list of their patients overdue for breast cancer screening and, if needed, took action to initiate a cascade of downstream events. 18,19 This model of care emphasizes management outside of office visits and provides a framework to facilitate the efficient allocation of limited clinical resources.…”
mentioning
confidence: 99%
“…23,24 We previously reported that our redesigned care process, which involved work with allied health staff, standardisation of care, and use of an electronic, webbased tool, significantly improved breast cancer screening for female patients in our practice without requiring additional physician or nurse time. 25 Appointment secretaries were trained to use the clinical informatics system PRECARES (PREventive CAre REminder System) to proactively contact patients before they were due for mammography and to schedule it at their convenience. PRECARES was next further developed to include tests that patients with diabetes need every 12 months (HbA1c, LDL, and urine microalbumin), as recommended by most national guidelines, 26 and also USPSTF-recommended adult preventive services.…”
Section: Introductionmentioning
confidence: 99%